Shock wave interactions : selected articles from the 22nd International Shock Interaction Symposium, University of Glasgow, United Kingdom, 4-8 July 2016 /: selected articles from the 22nd International Shock Interaction Symposium, University of Glasgow, United Kingdom, 4-8 July 2016. ([2018]) - Unknown
No abstract available